The Ameliorating Effect Of Co_Enzyme Q10 On Kidneys After Administration Of Ivermectin In Rabbits - Suhaib Ismail; Mohammed T,Wahda A.Kharofa (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The goal of the current research is to ascertain whether Coenzyme Q10 can prevent or mitigate damage to the kidney tissues that are harmed when rabbits are given ivermectin. In this investigation, 48 healthy adult male albino rabbits, weighing between 1350 and 1800 grams, who were between 13 and 14 weeks of age, were used. Eight animals each were split up into six identical groups by the groups.Control group A. Groups B, C, and D of rabbits received 2 mg/kg of the drug every week. After stopping ivermectin for eight weeks,. B: Perform direct tissue slicing; C: Give Coenzym q 10 (10 mg/kg) once daily for 30 days; D: Use rabbits Give self-healing 30 days. F = just Coenzym q10 10mg/kg for 30 days; E = ivermectin 2 mg/kg every week For eight weeks and 10 mg/kg of Coenzyme Q10.. The outcomes revealed The renal polycysts, inflammatory cells infiltration and necrosis of the renal tubules' lining epithelial cells, and atrophy or vaculation of glomeruli were among the damage to the kidneys observed histopathologically in groups B and D. The current study recommends that while administering ivermectin, reasonable caution should be taken. Secondly Ivermectin toxicity-related kidney damage is ameliorated by Coenzyme Q10.